2018
DOI: 10.3390/rs10101662
|View full text |Cite
|
Sign up to set email alerts
|

Using Single- and Multi-Date UAV and Satellite Imagery to Accurately Monitor Invasive Knotweed Species

Abstract: Understanding the spatial dynamics of invasive alien plants is a growing concern for many scientists and land managers hoping to effectively tackle invasions or mitigate their impacts. Consequently, there is an urgent need for the development of efficient tools for large scale mapping of invasive plant populations and the monitoring of colonization fronts. Remote sensing using very high resolution satellite and Unmanned Aerial Vehicle (UAV) imagery is increasingly considered for such purposes. Here, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 55 publications
(43 reference statements)
0
50
0
3
Order By: Relevance
“…The importance of using CHM to identify Phragmites, as it reduces both errors of omission and commission, is also clearly demonstrated, especially when CHM is combined with NDVI Oct . Several other studies showed the advantages of CHM [83][84][85]. The reduction of errors of omission and commission for Phragmites was observed in the study of Samiappan et al [33], where the author used the SVM classifier.…”
Section: Feature Selectionmentioning
confidence: 91%
“…The importance of using CHM to identify Phragmites, as it reduces both errors of omission and commission, is also clearly demonstrated, especially when CHM is combined with NDVI Oct . Several other studies showed the advantages of CHM [83][84][85]. The reduction of errors of omission and commission for Phragmites was observed in the study of Samiappan et al [33], where the author used the SVM classifier.…”
Section: Feature Selectionmentioning
confidence: 91%
“…Phragmites australis in estuaries by Abeysinghe et al (2019) and Fallopia spp. in floodplains by Martin et al (2018)).…”
Section: Discussionmentioning
confidence: 99%
“…In grasslands, invasive woody (Mirik et al 2013) and shrubby (Laliberte et al 2004;Ishii and Washitani 2013) species mapping has shown excellent results with satellite and airborne image classification. Meanwhile, using an unmanned aerial vehicle (UAV)-borne remotely sensed (RS) imaging was increasingly applied for invasive species mapping in the recent years in flood plains and coastal regions (de Sá et al 2018;Martin et al 2018;Abeysinghe et al 2019;Jianhui et al 2019). Cost-effectiveness, high spatial and temporal resolution and the increasing availability of various miniature sensors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pairing such models with field studies or experiments would provide especially valuable insights into the relationship between these species and erosive processes. Photogrammetric analyses can provide useful insights into general fluvial biogeomorphic dynamics (Hortobágyi et al, 2017), and satellite and unmanned aerial vehicles (UAVs) can accurately map knotweed s.l . (Martin et al, 2018). Utilizing both technologies could generate biogeomorphic insights specific to locations infested with knotweed s.l . Establishing and conducting small field studies in various locations using standardized techniques would permit inter‐regional comparisons of hydrological regimes and soil types. Organizations concerned with improving road/stream crossings could integrate knotweed s.l .‐related questions into infrastructure assessments.…”
Section: Future Researchmentioning
confidence: 99%